Integrasi Contextual Teaching and Learning (CTL) dan Edmodo dalam Pembelajaran Mengidentifikasi Informasi Teks Eksplanasi: Sebuah Kajian Konseptual - Toti Laksana Bhirawa; Venty Saskia Rohmalita (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
The presence of edmodo, as an impact of technological advancements in education, offers a valuable opportunity for Indonesian language learning, particularly in identifying information within explanatory texts. Utilizing Edmodo for this purpose requires an appropriate strategy, such as contextual teaching and learning. While previous studies have extensively explored Edmodo's utilization and contextual learning implementation, its application remains broad and predominantly focused on administrative or exact sciences rather than specific Indonesian language skills. Furthermore, research on contextual strategies continues to be dominated by conventional or offline settings. Based on these gaps, this study aims to integrate contextual strategies with Edmodo's features in an online learning environment for identifying information in explanatory texts. The research method employed is library research, utilizing a critical and in-depth analysis of relevant and linear scientific literature. The results indicate that integrating contextual strategies with Edmodo features can create an active, creative, effective, and fun learning ecosystem (PAKEM) for explanatory texts. Edmodo's features successfully accommodate the real-world exploration principles of contextual strategies, making the learning process more efficient and meaningful for students.